Small Noncleaved Cells, Burkitt Type, Non-Hodgkin Lymphoma with Clinical Presentation of Hypercalcemia - Case report - Nogueira, José Otho (2000)
This article reports a case of 60 year-old woman admitted to the emergency room with protracted vomiting and hypercalcemia of 19g/dL. Following correction of hypercalcemia with hidration, costicosteroids and biphosphonates, the established diagnosis was a Small Non-Cleaved Cell Burkittlike Lymphoma, a non-Hodgkin Lymphoma that has been rarely reported in such early stage. The authors also elaborate a brief review of the neoplasms more commonly associated with increased calcium serum levels.